ISOLATION, CHARACTERIZATION AND ANTIBIOGRAM OF BACTERIAL PATHOGENS ISOLATED FROM MILK OF COW, GOAT AND SHEEP (FULafia Journal of Science and Technology, 2017)
Bacteriological analyses of the milks of cow, sheep and goat were conducted in Keffi, North-Central Nigeria. The bacteriological analyses revealed the presence of Staphylococcus aureus, Escherichia coli, Klebsiella spp., Pseudomonas aeruginosa, Proteus vulgaris and Salmonella spp. This study also revealed a total heterotrophic count, total faecal count and coliform count (×104cfu/ml) in the cow, sheep and goats milk to be 4.8, 1.0 and 2.9; 4.5, 0.6 and 2.5; 3.6, 0.4 and1.6 respectively. However, rate of occurrences of the respective isolates indicate varying degree of occurrences. E. coli and Salmonella spp. had the highest occurrences of 86.7% each. Percentage occurrence in descending order is in the order: Staphylococcus aureus (80.0%), followed by Klebsiella spp. (73.3%), P. aeruginosa (66.7%), then Proteus vulgaris (33.3%)
Keywords: Isolation; antibiogram; bacteria; milk; Keffi